Critical Analysis of Sexual Harassment at Work Place (Prevention, Prohibition and Redressal) Act, 2013 with Special Emphasis to Film Industry - S', Anjana; George, Meera Elsa
Gone are the days where only men were the breadwinners of a family. With opportunities expanding and people moving forward into a contemporary world, gender disparity regardingemployment has become a thin line. We are in an era where both men and women workfor a living and contribute to theirfamily. Women are now coming forward and stepping into powerful positions and leaving their marks in various industries. However, there are many issues that demotivate women from coming forward. One such major issue is the absence of a healthy and safe working environment. Sexual Harassmentat Workplace is a violation of a woman's fundamental rights under Article 15, 19 and 21. It makes a woman insecure and causes severe mental trauma which in turn makes her quit the job or affects her self-confidence. Women are not sex toys for pleasure or the weak vulnerable section of humankind, but years of the patriarchalsystem that silenced women have resultedin women being subject to such exploitation.
Keywords: Irina